2021
DOI: 10.1039/d0fo02324h
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds: current industrial applications, limitations and future challenges

Abstract: Phenolic compounds are natural bioactive molecules found mainly in plant tissues that have shown interesting bioactivities, such as antioxidant, antimicrobial, anti-inflammatory, antiproliferative activities, among others, which has led to great...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
184
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 450 publications
(257 citation statements)
references
References 89 publications
1
184
1
5
Order By: Relevance
“…When it comes to industry implementation, these compounds are known to be added mainly in the cosmetic and food industry (Albuquerque et al 2021 ). Although they are in small amounts, extensive research on polyphenolic compounds has shown their applications in different foods imparting color, flavor, odor and bitterness.…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…When it comes to industry implementation, these compounds are known to be added mainly in the cosmetic and food industry (Albuquerque et al 2021 ). Although they are in small amounts, extensive research on polyphenolic compounds has shown their applications in different foods imparting color, flavor, odor and bitterness.…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…Bio-residues from fruits and vegetables generated during post-harvest treatments and processing steps, can be considered as interesting matrices for the recovery of bioactive molecules, such as phenolic compounds, organic acids, tocopherols, vitamins, dietary fibers, and fatty acids [1,2]. All of these molecules, with high added value in the market, can be potentially used in several industrial sectors, such as in the food processing industry for the formulation of novel functional foods or to be used as additives and also in the pharmaceutical industry as natural therapeutic alternatives, among others [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidants derived from natural sources have low stability and are easily degraded due to their highly sensitive nature (Carocho et al., 2015). Regulatory approval for only fewer antioxidants from natural sources is available (Albuquerque et al., 2021).…”
Section: Application Of Antioxidants From Natural Sources For Fish Fishery Product Preservationmentioning
confidence: 99%